2004
DOI: 10.1139/z04-146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of 16th-century whale bones prompts a revision of the impact of Basque whaling on right and bowhead whales in the western North Atlantic

Abstract: The North Atlantic right whale, Eubalaena glacialis (Müller, 1776), is one of the world's most endangered large cetaceans. It is widely believed that Basque whalers caused the most dramatic decline of this species in the western North Atlantic during the early-16th and 17th centuries. Previous osteological analysis of 17 historic bones suggested that 50% of the Basque harvest consisted of right whales and 50% of bowhead whales, Balaena mysticetus L., 1758. This 50:50 ratio has been used to estimate pre-exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 28 publications
3
72
3
Order By: Relevance
“…These findings suggest the maintenance of large populations in the northeast Atlantic prior to 19th century commercial whaling that almost extirpated this species. Crossing to the northwest Atlantic, genetic analysis of whale bones recovered from a sunken Basque galleon off Canada's Labrador coast revealed that 16th century Basque whalers were mainly hunting bowhead whales and not right whales (Eubalaena glacialis), as was earlier inferred from osteological studies of the same material (Rastogi et al 2004). These findings have prompted a revision of the impact of Basque whaling on both species.…”
Section: Ancient-dna Studies Of Arctic Marine Mammalsmentioning
confidence: 80%
“…These findings suggest the maintenance of large populations in the northeast Atlantic prior to 19th century commercial whaling that almost extirpated this species. Crossing to the northwest Atlantic, genetic analysis of whale bones recovered from a sunken Basque galleon off Canada's Labrador coast revealed that 16th century Basque whalers were mainly hunting bowhead whales and not right whales (Eubalaena glacialis), as was earlier inferred from osteological studies of the same material (Rastogi et al 2004). These findings have prompted a revision of the impact of Basque whaling on both species.…”
Section: Ancient-dna Studies Of Arctic Marine Mammalsmentioning
confidence: 80%
“…Those fluctuations allow for a reconstruction of the postglacial sea ice history in the area, where bowheads were forced out of habitat due to ice cover or allowed to expand their range into new habitat in the absence of ice cover. Evidence suggests Basque whalers harvested similar numbers of bowhead whales and right whales (Eubalaena glacialis) in the 16th century in the Strait of Belle Isle, a region far south of the present-day range of the bowhead whale, thus indicating a southward shift during the Little Ice Age (Cumbaa 1986, Rastogi et al 2004 Polar bears ranged much further south during periods of climatic cooling. The oldest subfossil finding from the Palaearctic is probably an ulna found at Kew Bridge, London, dated to 40 000-50 000 yr before present (BP; Kurten 1964).…”
Section: Distributionmentioning
confidence: 99%
“…Not only did whale oil light the streets of Europe and America, fuel economies, and lubricate factories, but the industry left most large whale species endangered (Clapham et al, 1999) and may have affected food webs across hemispheres (e.g., Springer et al, 2003; but see Wade et al, 2007). Although the means to assess how whaling may have impacted large whale species are limited, it has been demonstrated that DNA can be successfully extracted from historical whale bones (Tebbutt et al, 2000;Rastogi et al, 2004;Morin et al, 2006;Borge et al, 2007), teeth (Pichler et al, 2001;Morin et al, 2006) and baleen specimens (Rosenbaum et al, 1997;Eastop and McEwing, 2004). This represents an important step towards using historical specimens to evaluate pre-exploitation levels of genetic diversity, population sizes, and catch composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from whale bones found at Red Bay, Labrador, a primary 16th-century whaling port, revealed a predominance of bowhead whales, a finding that brought into question the assumption that right whales were a principal target in this region (Rastogi et al, 2004). In contrast to Cumbaa's (1986) osteological analyses of 17 whale humeri from the 16th century, which suggested that right whales accounted for half of the Basque catch, Rastogi et al's (2004) genetic species identification using sequence analysis of the mitochondrial cytochrome b gene (including the same specimens assessed by Cumbaa, 1986) indicated that only one humerus was from a right whale, and 20 were from bowheads (5% right, 95% bowhead).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation